2015
DOI: 10.1111/1365-2745.12411
|View full text |Cite
|
Sign up to set email alerts
|

Parental environmental effects due to contrasting watering adapt competitive ability, but not drought tolerance, in offspring of a semi‐arid annual Brassicaceae

Abstract: Summary1. Parental effects (PE) can be adaptive and improve offspring performance when parents and offspring experience similar environmental conditions. However, it is unknown whether adaptive PE exist also in habitats where such similarity is unlikely due to strong temporal variation. In particular, we do not know whether PE can adapt offspring to fluctuating levels of neighbour competition in such habitats.2. Here, we tested for adaptive PE in terms of two key environmental factors in a semi-arid annual sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 39 publications
1
30
0
Order By: Relevance
“…This distinction may seem small, but it has important implications. Even though precipitation can vary unpredictably across years, it can still cause a correlated effect on neighbour density in the offspring environment (Metz et al, 2015). Therefore, populations of annual plants that persist under these environmental conditions are expected to exhibit a parental environmental effect on between-year seed dormancy.…”
Section: Introductionmentioning
confidence: 99%
“…This distinction may seem small, but it has important implications. Even though precipitation can vary unpredictably across years, it can still cause a correlated effect on neighbour density in the offspring environment (Metz et al, 2015). Therefore, populations of annual plants that persist under these environmental conditions are expected to exhibit a parental environmental effect on between-year seed dormancy.…”
Section: Introductionmentioning
confidence: 99%
“…An 'easy' alternative may be to study responses to in situ temporal between-year variation in climatic conditions. While avoiding confounding effects in a similar way as experiments, the drawback of such temporal approaches may only be that erratic annual climatic variation differs from a consistent and directional change imposed by permanent experimental manipulations, namely temporal changes are inherent in ecosystems and thus selected for specific adaptations that in turn could veil responses to directional changes, such as buffering effects of seed dormancy (Tielb€ orger & Valleriani 2005; Lampei & Tielb€ orger 2010), large seed size (Metz et al 2010) or adaptive parental effects (Metz, von Oppen & Tielb€ orger 2015). Interestingly though, between-year variations in plant-plant interactions have repeatedly contradicted spatial trends even when performed in very similar study systems (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…as in coral reef fish; Hamilton et al 2008). Evolutionary theory predicts that adaptive phenotypic responses should arise when the new environment is predictable (Marshall et al 2010, Metz et al 2015 and the gradient in chlorophyll found in West Scotland is predictable over several generations (Fig. S3).…”
Section: −1mentioning
confidence: 99%